2008
DOI: 10.1016/j.bmc.2008.01.033
|View full text |Cite
|
Sign up to set email alerts
|

The structure-based design, synthesis and biological evaluation of DNA-binding bisintercalating bisanthrapyrazole anticancer compounds

Abstract: Anticancer drugs that bind to DNA and inhibit DNA-processing enzymes represent an important class of anticancer drugs. In order to find stronger DNA binding and more potent cytotoxic compounds, a series of ester-coupled bisanthrapyrazole derivatives of 7-chloro-2-[2-[(2-hydroxyethyl)methylamino]ethyl]anthra[1,9-cd]pyrazol-6(2H)-one (AP9) were designed and evaluated by molecular docking techniques. Because the anthrapyrazoles are unable to be reductively activated like doxorubicin and other anthracyclines, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…9 The bisanthrapyrazoles 1, 4, and 5 all increased DT m about the same as the parent 6. In our previous study on the analogous ester-linked bisanthrapyrazoles 4 we showed that the slope of a plot of DT m versus drug concentration for a bisintercalator is approximately twice that of the monomeric monointercalator 6. This is due to the bisintercalator occupying twice the number of intercalation sites on the DNA as had been previously shown from a comparison of the bisintercalator dye YOYO and its monomeric form YO-PRO.…”
Section: Effect Of the Bisanthrapyrazoles On The Thermal Denaturationmentioning
confidence: 97%
See 4 more Smart Citations
“…9 The bisanthrapyrazoles 1, 4, and 5 all increased DT m about the same as the parent 6. In our previous study on the analogous ester-linked bisanthrapyrazoles 4 we showed that the slope of a plot of DT m versus drug concentration for a bisintercalator is approximately twice that of the monomeric monointercalator 6. This is due to the bisintercalator occupying twice the number of intercalation sites on the DNA as had been previously shown from a comparison of the bisintercalator dye YOYO and its monomeric form YO-PRO.…”
Section: Effect Of the Bisanthrapyrazoles On The Thermal Denaturationmentioning
confidence: 97%
“…Following this we used molecular modeling to design and synthesize a series of bisanthrapyrazoles that contained a diester linkage joining two anthrapyrazoles together. 4 However, the biological data on these bisanthrapyrazoles suggested that the ester linkages were susceptible to hydrolysis, possibly through the action of cellular esterases. 4 We showed that these bisanthrapyrazoles had good cell growth inhibitory activity and the compounds with two or more methylene linkers formed bisintercalation complexes with DNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations